Îjâz of Al-Qur'an in Perspective of An Noursi and Its Implication Towards the Translation of Al-Qur'an - Baihaqi, Yusuf (Universitas Islam Negeri Raden Intan Lampung, 2019)
There was a debate among the scholars regarding whether Al-Qur’an text was possible to be translated or not. When Al-Qur’an text is translated, another problem arises, whether the translation has included the entire meaning contained in Al-Qur’an text. So, it whether can replace the position of Al-Qur’an text or not. This paper aims to address these problems in An Noursi's perspective. Based on a descriptive analytical literature review of the writings of An Noursi relating to Al-Qur'an and the translation of Al-Qur'an, a conclusion can be drawn that the An Noursi is classified by Ulama that the text of Al-Qur'an cannot be translated into any language . This perspective is clearly seen when he explained the theme of Al-Qur'an, where Al-Qur'an is an aspect of the miracles of the language possessed by Al-Qur'an and cannot be possessed and compared by any other language. In addition, An Noursi's rejection of Al-Qur'an translation above cannot be separated from the social political influence in Turkey at that time, where religious secularization was very intensively carried out by the authorities. In other words, this paper tries to present a moderate perspective about the translation of Al-Qur’an, where the process of translating Al-Qur’an is very possible when the translation is understood to be limited to Tarjamah Tafsîriyyah not Tarjamah Harfiyyah, because actually the translation of Al-Qur’an is intended by the Ulama the one who rejected it was Tarjamah Harfiyyah. Besides, the translation of Al-Qur’an meant by the Ulama who allowed it was Tarjamah Tafsîriyyah.